Public Policy and Economic Misery Nexus: A Comparative Analysis of Developed and Developing World - Audi, Marc; Ali, Amjad (International Journal of Economics and Financial Issues, 2023)
Minimizing the level of economic misery is one of the prime objectives of all economies for the last couple of decades. It is not individuals who can themselves control it, some public policy options provide roots to minimize economic misery. This article has examined the role of public policy in determining the level of economic misery among developed and developing countries from 1987 to 2019. The empirical findings of the article show level of domestic investment, foreign debt, and government revenue are discouraging economic misery among developing countries. Whereas economic development and the level of the population are encouraging economic misery among developing countries. The level of domestic investment is promoting economic misery in developed countries, but government revenue and economic development are reducing economic misery among developed countries. In the case of the whole sample analysis, the level of domestic investment and government revenues decreases the level of economic misery, but the level of population, foreign debt, and economic development depresses the economic misery. Thus, it is concluded that public policy plays important role in determining economic misery both in developed and developing countries. Developing countries should raise the level of domestic investment and government revenue to depress economic misery. Developed countries should raise government revenue and economic development to depress economic misery. So, for the reduction of economic misery in developed and developing countries, public policy must be strengthened.